3-D finite element analysis and experimental investigation of electrodynamic repulsion force in molded case circuit breakers - Xingwen Li, Xingwen Li; Degui Chen, Degui Chen (IEEE transactions on components and packaging technologies, 2005)
To the optimization design of molded case circuit breakers (MCCBs), it is necessary and important to calculate the electro-dynamic repulsion force acting on the movable conductor. With three-dimensional (3-D) finite element nonlinear analysis, according to the equations among current-magnetic field-repulsion force and taking into account the ferromagnet, contact bridge model is introduced to simulate the current constriction between contacts, so Lorentz and Holm force acting on the movable conductor and contact, respectively, can be combined to calculate. Coupled with circuit equations, the opening time of movable contact also can be obtained using iteration with the restriction of contact force. Simulation and experiment for repulsion force and opening time of five different configuration models have been investigated. The results indicate that the proposed method is effective and capable of evaluating new design of contact systems in MCCBs.